Theoretical evaluation of diffusivity of hydrogen in palladium and rhodium - Baykara, SZ (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
A formulation is developed for obtaining diffusivities of hydrogen in f.c.c. metals from cluster calculations of activation energies. Results for palladium compare reasonably well with medium temperature experimental values. A theoretical diffusivity curve is also suggested for hydrogen in rhodium. (C) 2004 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: diffusivity; hydrogen-palladium; hydrogen-rhodium; BCC METALS; LIGHT INTERSTITIALS; SILVER ALLOYS; PD(111); STATE; NB; TA; Chemistry; Electrochemistry; Energy & Fuels